Three-phase DC-AC converter with LCL filter for distributed microgeneration with null error in steady state - Silva, Viviane Barrozo da; Ricciotti, Antonio Carlos Duarte; Militão, Hebert Sancho Garcez; Militão, Júlio Sancho Teixeira; Siliprandi, Álvaro Daniel Hartmann; Silva, Wilson Domingos e; Júnior, Adailton Braga; Luz, Lillian Kathleen Dias; Aguiar, Sandra da Cruz Garcia do Espírito Santo; Veiga, Diego Lima (International Journal of Advanced Engineering Research and Science, 2020)
This article presents a digital control for a three-phase DC-AC converter with four wires with LCL filter that makes up the inverter module of a distributed microgeneration system, which guarantees a zero error in a permanent regime and can be connected to any generation and minimizes high-frequency current harmonics injected into the network. The inverter control system is based on a triangular carrier, which uses: an internal mesh to control the grid current. In the simulated tests, good functioning of this control technique was verified, even when faced with the variation of the impedance of the distribution network in the PCC, a satisfactory response of the dynamic behavior of the control system was obtained with the efficient control of the active and reactive power and the guarantee of a null error on a steady state.